Vector competence of anthropophilic mosquitoes for a new mesonivirus in Senegal - Alioune Gaye; Moussa Moïse Diagne; El Hadji Ndiaye; Marie Henriette Dior Ndione; Martin Faye; Cheikh Talla; Gamou Fall; Yamar Ba; Diawo Diallo; Ibrahima Dia; Pascal Handschumacher; Ousmane Faye; et al. (Emerging Microbes and Infections)
The mesoniviruses (MESOVs) belong to the newly described Mesoniviridae family (Order: Nidovirales). They have never been reported in Senegal until recently during a study in arbovirus emergence with the detection of a new species of MESOV named Dianke virus (DKV) from common mosquitoes from eastern Senegal. Actually, their vector competence for this newly described DKV is unknown. We, therefore, estimated the vector competence of Culex tritaeniorhynchus, Culex quinquefasciatus, Aedes aegypti, and Anopheles gambiae mosquitoes collected in Senegal for DKV using oral infection. Whole bodies, legs/wings, and saliva samples were tested for DKV by RT–PCR to estimate infection, dissemination, and transmission rates. The infectivity of virus particles in the saliva was confirmed by infecting C6/36 cells. Virus transmission rates were up to 95.45% in Culex tritaeniorhynchus, 28% in Cx. quinquefasciatus and 9.09% in Aedes aegypti. Viral particles in the saliva were confirmed infectious by C6/36 cell culture. An. gambiae was able to disseminate DKV only at 20 days post-infection. This study shows that Culex mosquitoes are more competent than Ae. aegypti for DKV, while Anopheles gambiae is not likely a competent vector.